2003
DOI: 10.1021/la035596t
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant Aggregation within Room-Temperature Ionic Liquid 1-Ethyl-3-methylimidazolium Bis(trifluoromethylsulfonyl)imide

Abstract: On the basis of the response of solvatochromic probes [Reichardt's betaine dye, pyrene, and 1,3-bis(1-pyrenyl)propane], we have investigated the aggregation behavior of common anionic, cationic, and nonionic surfactants when solubilized within a low-viscosity room-temperature ionic liquid 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide (emimTf2N). We observed possible aggregate formation by all nonionic surfactants included in the study (Brij-35, Brij-700, Tween-20, and Triton X-100), while no ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
246
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 331 publications
(257 citation statements)
references
References 19 publications
8
246
0
3
Order By: Relevance
“…Seyrek et al [31] have shown that the binding constant in the system of -lactoglobulin-poly(vinylsulfate) was inversely related to persistence length of poly(vinylsulfate) chain implying that protein binding to their characteristic hydrophobic-hydrophilic balance, ILs are widely used as surface active agents to study micellization behaviour in water [38][39][40][41][42]. In addition, this particular attribute makes these liquids compatible with many common solvents thereby generating designer solvents with controlled hydrophobicity, polarity and miscibility.…”
Section: Effect Of Persistence Lengthmentioning
confidence: 99%
See 1 more Smart Citation
“…Seyrek et al [31] have shown that the binding constant in the system of -lactoglobulin-poly(vinylsulfate) was inversely related to persistence length of poly(vinylsulfate) chain implying that protein binding to their characteristic hydrophobic-hydrophilic balance, ILs are widely used as surface active agents to study micellization behaviour in water [38][39][40][41][42]. In addition, this particular attribute makes these liquids compatible with many common solvents thereby generating designer solvents with controlled hydrophobicity, polarity and miscibility.…”
Section: Effect Of Persistence Lengthmentioning
confidence: 99%
“…Ionic liquids and their solutions are being used as biocatalytic reaction media, biosensors, protein and enzyme stabilizers etc. [41,42]. Numerous studies have explored protein and enzyme stability in these solvents that conclude that the observed catalytic activity of enzymes was due to the heterogeneously dispersed state of enzymes [43][44][45][46].…”
Section: Effect Of Persistence Lengthmentioning
confidence: 99%
“…Relative studies on the aggregation of nonionic surfactants in ILs have been reported (Evans et al, 1982;Evans et al, 1983b;Fletcher & Pandey, 2004;Gao et al, 2009b;Li et al, 2008b;Patrascu et al, 2006;Wu et al, 2008). Masahiro et al (Moniruzzaman et al, 2008) reported the formation of reverse micelles in [C 8 mim][Tf 2 N] comprising sodium bis(2-ethyl-1-hexyl) sulfosuccinate (AOT) as surfactant with 1-hexanol as a cosurfactant.…”
Section: Effects Of Ionic Liquids On the Formation Of Supramolecular mentioning
confidence: 99%
“…Así mismo, la CMC depende de diversos factores, tales como la estructura del líquido iónico, la forma en que se constituyen los agregados y las características del medio en el cual se solubiliza el líquido iónico. 2 En este sentido, la temperatura y la presencia de sales afectan el proceso de agregación.…”
Section: Introductionunclassified
“…En consecuencia, es posible transformar la ecuación empírica de Stauff-Klevens, usando logaritmo neperiano en lugar del logaritmo decimal, de la siguiente manera: (2) A partir de los datos de la literatura para diversos líquidos iónicos de la familia 1-alquil-3-metil-imidazolio con dos aniones diferentes, cloruro y bromuro, se observa en la Figura 1 un comportamiento similar al presentado al graficar la CMC como función del número de átomos de carbono de la cadena carbonada.…”
unclassified